Stability of maize to source material bubble smut and its harmfulness in the south forest-steppe zone of Ukraine - Харченко, Л. Я.; Холод, С. М.; Іллічов, Ю. Г. (Scientific Progress & Innovations, 2012)
The characteristic of introduced genotypes of maize for resistance to smut diseases. An analysis of 48 samples of corn defeat various groups of ripeness. Confirmed by the data that the main influence on the development of corn smut disease had abiotic factors, particularly temperature and precipitation. The structural analysis of the yield on the parameters: the mass of grain per ear, grain number, weight of 1000 grains. Substantial grain losses were observed in lesions of 5% of plants, and in lesions of 40% yield practically non formed. Allocated to the samples, which are sources of resistance to bubble smut, which can be used in breeding maize for resistance to the disease.